The Environmental Squad performance in the state of Sergipe for purposes of environmental education against environmental issues. - Costa, Cristiano Cunha (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708815 The Environmental Squad operates based on environmental legislation performing policing to promote the protection of the environment. This work aimed to study the performance of Environmental Military Police Squad of Sergipe for purposes of environmental education forward the environmental issues. For this, it was made a survey of the activities performed by the Environmental Squad. The Environmental Squad operates in ostensive patrolling, both in repressive and preventive ways: river patrolling, peace disturbance, wildlife trafficking, illegal exploitation of forest resources, illegal exploitation of mineral resources and environmental education activities. Therefore, it is a specialized unit of great importance with regard to the protection of the environment in the State of Sergipe, actively functioning according to the peculiarities of each occurrence in favor of the environment and quality of life. It requires the development of environmental education in dynamic character and permanent basis, taking into account the environment in its multiple and complex relationships, involving ecological, psychological, legal, political, social, economic, scientific, cultural and ethical.